Sinergi Keselamatan dan Lingkungan Kerja untuk Mendukung Produktivitas dan Kesejahteraan Berkelanjutan di Sektor Pelabuhan - Hengki Firmansyah; Muji Gunarto; Andriyansah Andriyansah (Society, 2024)
A sustainable work environment is pivotal in enhancing employee productivity, particularly in the port sector, which faces high occupational risks and complex operational demands. This study aims to analyze the impact of occupational health and safety (OHS) and the work environment on employee productivity at Pelabuhan Indonesia PT (Persero) II, Tanjung Pandan Branch. A quantitative approach was employed using a survey method with structured questionnaires completed by 37 respondents, analyzed through Structural Equation Modeling-Partial Least Square (SEM-PLS). The research variables included OHS dimensions (workplace conditions, safe behaviors, psychological atmosphere) and work environment factors (lighting, air temperature, noise, workspace, safety). The analysis revealed that OHS significantly influences productivity (p < 0.05), with a greater contribution from the psychological atmosphere dimension than other technical aspects. The work environment also positively affects productivity, with lighting and workplace safety emerging as the most significant contributors to fostering a supportive work atmosphere. These findings underscore the importance of a conducive work environment, supported by employee security and comfort, in boosting motivation and operational efficiency. The study’s social implications highlight that investments in OHS programs and workplace improvements enhance productivity, foster harmonious workplace relationships, reduce conflicts, and strengthen employees’ social well-being. Together, these variables account for 68% of the variance in employee productivity, emphasizing the critical role of OHS and work environment management in improving operational efficiency. This study offers practical recommendations to strengthen OHS programs through regular training, stringent supervision, and infrastructure enhancements that ensure employee comfort. These results are expected to reference other local ports in developing policies integrating workplace safety and environmental management to achieve sustainable productivity.